2013
DOI: 10.1177/0748233713506769
|View full text |Cite
|
Sign up to set email alerts
|

The biochemical and histological effects of lichens in normal and diabetic rats

Abstract: Oxidative stress plays an important role in causing diabetes; however, no studies have thoroughly reported on the toxic and beneficial effects of lichen extracts in patients with diabetes mellitus (DM). This study covers a previously unrecognized effect of two well-known lichen species Cetraria islandica and Pseudevernia furfuracae in streptozotocin (STZ)-induced diabetes. In experimental design, control or diabetic rats were either untreated or treated with aqueous lichen extracts (250-500 mg/kg /day) for 2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Previous studies 68 - 70 focused on possible anti-diabetic effects of Cetraria islandica and Pseudevernia furfuracea extracts in streptozotocin-induced diabetes in rats. Although investigators recommended low-dose C. islandica for early intervention in type 1 diabetes mellitus, the extracts did not improve diabetes-related parameters in rats.…”
Section: Pharmacological Activities Of Lichensmentioning
confidence: 99%
“…Previous studies 68 - 70 focused on possible anti-diabetic effects of Cetraria islandica and Pseudevernia furfuracea extracts in streptozotocin-induced diabetes in rats. Although investigators recommended low-dose C. islandica for early intervention in type 1 diabetes mellitus, the extracts did not improve diabetes-related parameters in rats.…”
Section: Pharmacological Activities Of Lichensmentioning
confidence: 99%
“…Moreover, the aqueous extract of Cetraria islandica decreased the total oxidative stress (TOS) and increased the total antioxidant capacity (TAC) in streptozotocin-induced Diabetes Mellitus type 1 Sprague-Dawley rats [ 118 ]. Using the same model, the aqueous extract of Cetraria islandica (250–500 mg/kg/day) increased the levels of SOD, CAT and GSH, and reduced the levels of MDA [ 16 , 119 , 120 ]. Regarding neuroprotection studies, the protective role of Cetraria islandica and its isolated secondary metabolite fumarprotocetraric acid has been demonstrated in a hydrogen peroxide-induced oxidative stress model on human U373MG astrocytoma cells and human SH-SY5Y neuroblastoma cells.…”
Section: Therapeutic Potentialmentioning
confidence: 99%
“…98 In vitro studies on the effect of aqueous extracts of Cetraria islandica against diabetes-induced oxidative stress have revealed that this extract, at 5 and 10 mg mL À1 , increased antioxidant capacity in blood cultures of patients with diabetes; 99 however, no benecial effects on antioxidant status were found in diabetic rats treated intraperitoneally with 250-500 mg per kg per day of Cetraria islandica aqueous extract for 2 weeks. 100 In addition to C. islandica, the lichen specie Parmelia perlata afforded antidiabetic effect by stimulating insulin secretion. 92 Halici et al 70 demonstrated the potential gastroprotective effect of the aqueous extract of Usnea longissima against indomethacin-induced gastric lesions in rats through an antioxidant mechanism.…”
Section: Other Activitiesmentioning
confidence: 99%